Educational program for the control of modifiable risk factors of breast cancer in women - Álvarez Perulena, Lourdes (2023)
Breast cancer is the second most common malignant neoplasm in women and is a global health problem. A developmental, longitudinal, prospective research study was carried out in the family doctor's office 31, of the 50th Anniversary Polyclinic of Nicaragua, Cuba from January 2018 to January 2021, with the objective of designing an educational program for the control of risk factors. modifiable risk of breast cancer in women. From a population of 128 women aged 25 to 75 years and over, a sample of 25 women was selected according to non-probabilistic sampling by criteria. It used descriptive statistics. In the study carried out, the age of 55 to 64 years prevailed, with a basic secondary school level. The results achieved show that women have risk factors for breast cancer, such as early menarche, alcohol consumption, smoking, and history of third-generation breast pathologies. The educational program consisted of four topics in six sessions and was evaluated as acceptable by specialist criteria. The educational program designed for the control of modifiable risk factors for breast cancer in women has an educational and transformative approach as it addresses the generalities of breast cancer, its risk factors, cancer prevention, and breast self-examination with projection group and systemic character.